Wear Rate and Hardness of Boride Low Carbon Steel - Jabbar Hussein Mohmmed (Journal of Engineering, 2015)
There are no single materials which can withstand all the extreme operating conditions in modern technology. Protection of the metals from hostile environments has therefore become a technical and economic necessity. In this work, for enhancing their wear-resistance, boride layers were deposited on the surface of low carbon steel by a pack cementation method at 850 °C for (2, 4, and 6) h using vacuum furnace. The boronizing process was achieved using different concentration of boron source (20, 25, and 30) % wt. into coating mixture to optimize the best conditions which ensure the higher properties with lower time. The coating was characteristic by X ray diffraction (XRD), and it is confirmed the presence of (Fe2B) and (FeB) in the coating. The wear rate, hardness and thickness of the boride layers were measured, and it was observed that they effected by concentration of boron and time holding of boronizing process. Experimental results show that the higher properties of coating layer were obtained with 30% wt. of boron concentration and 4 h time holding.